2011
DOI: 10.3892/or.2011.1499
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic alteration of β-catenin and c-kit expression by imatinib in p16-positive squamous cell carcinoma compared to HPV-negative HNSCC cells in vitro

Abstract: Abstract.The most common neoplasm arising in the upper aerodigestive tract is head and neck squamous cell carcinoma (HNSCC). Tumor growth, invasion and systemic dissemination is a multistep process of dysregulated cellular signaling pathways and an altered cell-cell and cell-matrix interaction. Aberrant Wnt/β-catenin signaling is linked to tumor development and dissemination in several tumor entities. β-catenin is a multifunctional protein within the canonical Wnt pathway, which is an important factor for redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…In the study by Schultz et al [ 29 ], the expression of the Beta-Catenin as well as of the c-kit was assessed in p16-positive, and HPV-negative HNSCC treated with imatinib. However, this study lacks in vitro analyses of the therapeutic potential of the Wnt/Beta-Catenin signaling blockade.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Schultz et al [ 29 ], the expression of the Beta-Catenin as well as of the c-kit was assessed in p16-positive, and HPV-negative HNSCC treated with imatinib. However, this study lacks in vitro analyses of the therapeutic potential of the Wnt/Beta-Catenin signaling blockade.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HNSCC presents a high propensity to develop local recurrence following treatment ( 40 ). Concomitant CTR treatment has been previously demonstrated to increase the overall and five-year survival rate of patients with HNSCC at advanced stages, and offer better locoregional control rate ( 29 ). To further improve the survival rates for patients with HNSCC, particularly those presenting with unresectable HNSCC, innovative strategies and targeted therapies must be explored ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the multifunctional protein β-catenin is one of the most important factors for reducing cell-cell interactions in malignant epithelial cells ( 28 , 29 ). However, previous studies have reported that β-catenin participates in the development of HN cancer via a nuclear downstream effector of the canonical wingless-related integration site (WNT)-signalling cascade ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological, genetic, molecular and clinical profile of HPV-associated HNSCC cells appears to differ from that of tobacco and alcohol-induced HNSCC (non-HPV). HPV-positive oropharyngeal carcinomas are characterized by young age at onset, male predominance, and strong association with sexual behaviour (11,12). Kreimer and colleagues (13) analysed study locations and found that HPV prevalence of oral SCCs was similar in Europe (16.0%) and North America (16.1%) but significantly greater in Asia (33.0%).…”
Section: Introductionmentioning
confidence: 96%
“…The expression of E6 and E7 inhibits two tumoursuppressor proteins: p53 and retinoblastoma protein (pRb). The loss of several key regulative proteins activates dedifferentiation, proliferation and cell cycle progression of HPV-infected epithelial cells and facilitates induction of the transformed phenotype (12,16). Loss of cell adhesion and transformation of epithelial cells to a mesenchymal phenotype is described as epithelialmesenchymal transition (EMT).…”
Section: Introductionmentioning
confidence: 99%